Growth and Yield of Spinach (Amaranthus tricolor L.) Using Various Compositions of Planting Media - Fitra Fadhilah Rizar; Maria Fitriana; Teguh Achadi (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2023)
Spinach was a vegetable that was rich in nutrients and has many health benefits. The high level of public consumption of spinach plants in line with population growth, it was necessary to increase production by using organic fertilizers. This research aimed to determine the effects of the composition of the growing media among soil, chicken manure, and oil palm empty fruit bunches fertilizer on the growth and yield of spinach. The research used a completely randomized design (CRD) with 6 treatments repeated three times and each treatment unit consisted of 5 plants so that the total number of all plants was 90 plants. The results of the analysis of diversity showed that the treatment of chicken manure and oil palm empty fruit bunches fertilizer had a very significant effect on the plant height, leaf area, plant fresh weight, crown fresh weight, root fresh weight and plant dry weight. The provision of chicken manure and oil palm empty fruit bunches fertilizer had a significant effect on the number of leaves, but had no significant effect on the level of greenness of the leaves and the root shoot ratio. The results of the study showed that the soil treatment: chicken manure: oil palm empty fruit bunches fertilizer (1:2:2) provided the best results on the variables of plant height, number of leaves, leaf area, plant fresh weight, crown fresh weight, root fresh weight, and plant dry weight. The soil composition : chicken manure : oil palm empty fruit bunches fertilizer (1:2:2) was the best combination of planting media for the spinach growth and yield. Spinach cultivation using the composition of soil planting media, chicken manure, oil palm empty fruit bunches (1:2:2) could increase crop yields.